Local working collections as the foundation for an integrative conservation of Theobroma cacao L. in Latin America - Lavoie, Andreanne; Thomas, Evert; Olivier, Alain (Frontiers Media, 2023)
The intraspecific diversity of cacao has traditionally been preserved in genebanks. However, these establishments face various challenges, notably insufficient funding, accession redundancy, misidentification and lack of wild cacao population samples. In natural environments, it is expected that unknown varieties of cacao may still be found, but wild populations of cacao are increasingly threatened by climate change, deforestation, habitat loss, land use changes and poor knowledge. Farmers also retain diversity, but on-farm conservation is affected by geopolitical, economic, management and cultural issues, that are influenced at multiple scales, from the household to the international market. Taking separately, ex situ, in situ and on-farm conservation have not achieved adequate conservation fostering the inclusion of all stakeholders and the broad use of cacao diversity. We analyze the use of the traditional conservation strategies (ex situ, in situ and on-farm) and propose an integrated approach based on local working collections to secure cacao diversity in the long term. We argue that national conservation networks should be implemented in countries of origin to simultaneously maximize alpha (diversity held in any given working collection), beta (the change in diversity between working collections in different regions) and gamma diversity (overall diversity in a country).